Utilizing Integrated Marketing Strategies to Enhance the Competitiveness of Higher Education Institutions - Shakhlo Raupovna Ruziyeva (Academia Open, 2026)
The intensifying competition in the global higher education market has compelled higher education institutions to move beyond traditional promotional practices and adopt integrated marketing strategies that address credibility, differentiation, and stakeholder expectations. This study aims to examine how integrated marketing strategies, combining the traditional marketing mix with public trust and strategic partnerships, contribute to enhancing the competitiveness of higher education institutions. The research employed a mixed-methods design using survey data collected from 146 respondents, including students, parents, and administrative staff from higher education institutions in the Bukhara region. The data were analyzed systematically through SWOT and STEPLED frameworks to capture internal capabilities and external environmental dynamics influencing institutional competitiveness. The findings demonstrate that integrated marketing strategies significantly strengthen institutional competitiveness by improving brand image, reinforcing public trust, and supporting sustainable strategic positioning. Digital marketing adoption, alumni engagement, and inter-institutional partnerships emerged as key drivers of competitive advantage, while limitations in professional marketing capacity and financial resources remained critical challenges. The novelty of this study lies in empirically integrating public trust and strategic partnerships into the classical marketing mix within a unified analytical model tailored to a transitional higher education context. The results provide theoretical contributions to higher education marketing literature and offer practical and policy-relevant implications for university leaders seeking to design evidence-based, sustainable marketing strategies that enhance competitiveness in both regional and international higher education markets.Keywords : Integrated Higher Education Marketing, Institutional Competitiveness, Public Trust Governance, Strategic University Partnerships, Institutional Brand ReputationHighlight : Integrated marketing, public trust, and partnerships jointly strengthen higher education institutional competitiveness. Brand image and public trust directly shape stakeholder perceptions and student choice decisions. Digital marketing adoption and strategic partnerships consistently improve institutional positioning in competitive education markets.